PENGARUH FINANCIAL DISTRESS, CAPITAL INTENSITY, DAN THIN CAPITALIZATION TERHADAP TAX AVOIDANCE DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Ananda, Fuzi Rizky; Purwasih, Desy (LPPM Universitas Bina Bangsa, 2025)
This research aims to test whether there is an influence of financial distress, capital intensity, and thin capitalization on tax avoidance with company size as a moderating variable. The population in this study are energy sector companies listed on the Indonesian stock exchange. The number of samples in this research was 15 companies. The sampling technique uses a purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis with the E views 13 application. The results of this research provide empirical evidence that financial distress has no effect on tax avoidance, capital intensity has an effect on tax avoidance, thin capitalization has an effect on tax avoidance, company size cannot moderate the effect of financial distress, capital intensity, and thin capitalization on tax avoidance.